2020
DOI: 10.1037/scp0000240
|View full text |Cite
|
Sign up to set email alerts
|

Psychological evaluation of Catholic seminary candidates: Strengths, shortcomings, and an innovative plan.

Abstract: The ongoing clergy sexual abuse crisis in the Catholic Church has led to calls for major changes in the psychological evaluation of seminary applicants. Unfortunately, there is increasing agreement that current, standard psychological testing is not effective in ferreting out sexual difficulties in the general population, much less in seminary candidates. This article addresses both the strengths and shortcomings of the current evaluation process, as well as within the ecclesial system. We begin with a review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Additionally, bishops have shied away from recommending which tests to use, respecting the psychological community’s expertise. Second, Church efforts have been limited by the lack of widespread knowledge, or acceptance, of what guidelines the Church has issued, either by psychologists or particular dioceses and religious orders (McGlone et al, 2010; McGlone & Sperry, in press; Ortiz & McGlone, 2015). This general lack of consistency among test batteries, lack of agreement of what to measure, limitations in identified measures/variables that can predict health or future problems in seminarians, and what constitutes an adequate psychological profile for someone entering religious life, needs to be further developed and analyzed.…”
Section: Utility Of Rorschach In Seminary Candidate Evaluationsmentioning
confidence: 99%
“…Additionally, bishops have shied away from recommending which tests to use, respecting the psychological community’s expertise. Second, Church efforts have been limited by the lack of widespread knowledge, or acceptance, of what guidelines the Church has issued, either by psychologists or particular dioceses and religious orders (McGlone et al, 2010; McGlone & Sperry, in press; Ortiz & McGlone, 2015). This general lack of consistency among test batteries, lack of agreement of what to measure, limitations in identified measures/variables that can predict health or future problems in seminarians, and what constitutes an adequate psychological profile for someone entering religious life, needs to be further developed and analyzed.…”
Section: Utility Of Rorschach In Seminary Candidate Evaluationsmentioning
confidence: 99%
“…A strong collaborative relationship can assist the psychologist in understanding the values, strengths, and characteristics that are desired by the diocesan or religious community. Thus, the psychological evaluation would be ideally tailored to the specific community and provide an “assessment of fit” that enhances the stated purposes outlined above (McGlone & Sperry, 2020). Various models of collaboration may guide psychologists in interactions with clergy representations.…”
Section: Frequently Asked Questionsmentioning
confidence: 99%
“…While there are no universally accepted and standardized testing batteries, there are helpful guidelines offered by the USCCB’s Office of Consecrated Life as well as published research that offers suggested protocols for psychologists to use (McGlone & Sperry, 2020; Plante & Boccaccini, 1998; USCCB, 2015). These guidelines offer suggestions and best practices but do not mandate a particular protocol to follow.…”
Section: Frequently Asked Questionsmentioning
confidence: 99%
See 2 more Smart Citations